Multiwalled Carbon Nanotube-Chitosan Scaffold: Cytotoxic, Apoptoti c, and Necrotic Effects on Chondrocyte Cell Lines - Ilbasmis-Tamer, Sibel; Ciftci, Hakan; Turk, Mustafa; Degim, Tuncer; Tamer, Ugur (Current Pharmaceutical Biotechnology, 2017)
Background: Carbon nanotubes (CNTs) have been considered highly successful and proficient in terms of their mechanical, thermal and electrical functionalization and biocompatibility. In regards to their significant extent in bone regeneration, it has been determined that CNTs hold the capability to endure clinical applications through bone tissue engineering and orthopedic procedures. In the present study, we report on a composite preparation, involving the use of CNT-chitosan as scaffold for bone repair and regeneration. Through the use of water-soluble tetrazolium salt (WST-1) and double staining methods, the cytotoxic, necrotic, and apoptotic effects of chitosan-multiwalled carbon nanotube nanocomposites on the chondrocyte ATTC cell line have been exhibited. Methods: The chitosan-multiwalled carbon nanotube scaffolds were prepared. Chondrocytes differentiation tool (ATCC) cell line was prepared. WST-1 assay for cytotoxicity studies were performed by using chondrocytes cells in 12.5-200 μL concentration range. The samples of membranes (chitosan– multiwalled carbon nanotube scaffold) were measured at 2 mg/mL and further prepared amongst chitosan– multiwalled carbon nanotube scaffold’s which were placed into separate wells. While in the process of incubation, in the four-hour time range, the plates were immediately read in an Elisa microplate Reader. To predict the number of apoptotic and necrotic cells in culture, the technique of double staining with Hoechst dye was performed with PI on the basis of scoring cell nuclei. The mechanical properties such as tensile strength and elongation at break values of the chitosan only and chitosan/CNT scaffolds were evaluated on Texture Analyzer. Results: Based on the results of the WST-1 assay procedure, the amount of cell viability was not significantly affected by nanocomposite concentrations and the lowest mortality rate of cells was obtained at a concentration of 12.5 μg/mL, whereas the highest mortality rate was obtained at a rate of 200 μg/mL. In addition, the effects of chitosan-CNT nanocomposites were not found to cytotoxic on chondrocyte cells. The double staining method has been able to determine the apoptotic and necrotic effects of chitosan MWCNT nanocomposites. The apoptotic and necrotic effects of the combined compounds had varied within the concentrations. In a similar manner to the outcome of the control groups, apoptosis was obtained at a percentage of 2.67%. Under a fluorescent inverted microscope, the apoptotic cell nuclei were stained with a stronger blue fluorescence in comparison to non-apoptotic cells, which may have had an effect. We also compared the strain-stress curve measurements results. The results indicated that the mechanical properties of scaffold were not different. Elongation at break values increased by addition of CNT. Conclusion: CNTs as a biomaterial hold the potential to be used for applications in future regenerative medicine. By using the components of chondrocytes (ATTC) cell lines, the cytotoxicity evaluations were made for the chitosan-multiwalled carbon nanotube scaffold. The chitosan-MWCNT nanocomposites do not seem to induce drastic cytotoxicity to the chondrocyte cells.
Keywords: scaffold